Differences in Ecological Footprint Among Students Based on Socio-Economic Background and Gender - Mohamad Isnin Noer (Universitas Negeri Jakarta, 2016)
Studies examining the gender differences on environment issues are still scarce. Limited number of published studies have merely examined on the influence of gender on environmental knowledge and behaviour, particularly of their understanding on climate change. Hence, there remains a curious silence on gender relations in the mainstream literature and policy discourse. Here, the effect of gender on environmental using Ecological Footprint Analysis were evaluated on students at State University of Jakarta. Also, this study sought the contribution of socio-economic background on gender inequities. To account for Ecological Footprint of students, ex-post facto methods was used on 230 students to record their consumption behaviour. Result of Ecological Footprint calculation explained that all students enrolled in this University require 13.376,68 gHa/year of land to support their on-campus activities. On average, Ecological Footprint between males and females was not significantly different. The differences between males and females was also not significant as when socio-economic background taken into account.